Formes musicales dans le texte littéraire — analyse des Nouvelles orientales de Marguerite Yourcenar - Stráner, Zsófia (Verbum – Analecta Neolatina, 2008)
There exists an evident and organic connection between the various arts (for example, painting, sculpture, music, dance, literature, film etc.), which can be expressed with the term inter-art. This paper will be concerned with the relation between music and literature, more precisely, it examines the manifestation and the parallels of individual musical forms and renderings in literary text. The selected prose - Marguerite Yourcenar’s Oriental Tales - will be the focus of this textual-musical analysis, concentrating on those stylistic characteristics and text formatting tools that exhibit musical features in their properties and their structure. Even up to the present, analyses of literary texts have employed musical terms, for instance, polyphony, rhythm, cadence, pedal point, etc. This study will explore the textual manifestation of the following musical terms: rhythm, upbeat, non legato, imitation, tempo, lento, accelerando, retardation, polyphony, a cappella, soloist and figuration.